Karakteristik dan kualitas semen sapi Sumba Ongole dalam pengencer BTS yang dimodifikasi dengan susu kedelai - Alphonsius Umbu Jara Lodu; Alexander Kaka; Iven Patu Sirappa (Universitas Sulawesi Barat, 2021)
This study aimed to find out the quality of fresh semen from Sumba Ongole (SO) bulls which was diluted with Bestvile Thawing Solution (BTS) diluent modified with soybean milk (SKD). The study used a completely randomized design consisting of four treatments and 5 replications, P0 (100 % BTS), P1 (95 % BTS + 5 % SM), P2 (90 % BTS + 10 % SM), and P3 (85 % BTS + 15 % SM). The parameters observed were the colour, smell, consistency, pH, volume, motility, viability, and abnormalities of spermatozoa. The results showed that the characteristics were in the normal, creamy white semen colour, semen volume 3,6 ml, medium consistency, pH 6,3, typical SO bulls smell, sperm motility 85 %, mass activity +++, sperm concentration 1276 million/ml, live sperm 90,05 % and sperm abnormalities 6,15 % and quality there was no significant difference between the four treatments. The spermatozoa motility and viability in each treatment was able to which achieved on day 1. The characteristics of the spermatozoa of SO bulls were in the normal category. Meanwhile, BTS diluent with the addition of SKD was unable to maintain sperm quality.